Monitoring the Outcome of Phonosurgery and Vocal Exercises with Established and New Diagnostic Tools. (23rd January 2020) - Seipelt, Matthias; Möller, Andreas; Nawka, Tadeus; Gonnermann, Ute; Caffier, Felix; Caffier, Philipp P.
Abstract : Instrument-assisted measuring procedures expand the options within phoniatric diagnostics by quantifying the condition of the voice. The aim of this study was to examine objective treatment-associated changes of the recently developed vocal extent measure (VEM) and the established dysphonia severity index (DSI) in relation to subjective tools, i.e., self-evaluation via voice handicap index (VHI-12) and external evaluation via auditory-perceptual assessment of hoarseness ( H ). The findings for H (3 raters' group assessment), VHI-12, DSI, and VEM in 152 patients of both sexes (age range 16–75 years), taken before and 3 months after phonosurgery or vocal exercises, were compared and correlated. Posttherapeutically, all of the recorded parameters improved (p < 0.001 ). The degree of H reduced on average by 0.5, the VHI-12 score sank by 5 points, while DSI and VEM rose by 1.5 and 19, respectively. The correlations of these changes were significant but showed gradual differences between H and VHI-12 ( r  = 0.3), H and DSI ( r  = −0.3), and H and VEM ( r  = −0.4). We conclude that all investigated parameters are adequate to verify therapeutic outcomes but represent different dimensions of the voice. However, changes in the degree of H as gold standard were best recognized with the new VEM.